PENGUJIAN FAKTOR-FAKTOR YANG MEMPENGARUHI TRUST DAN KOMITMEN DALAM HUBUNGAN ANTARA PEMASOK DAN PERUSAHAAN : Studi Empiris pada Industri Garmen di Indonesia - Bujang . (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2007)
This study examine of importance factors that can be used to increase trust and commitment in collaborative relationship between suppliers with enterprise. Those factors are adaptation ability between supplier with enterprise (adaptation), generator a bond relation (bonds), costs that appeared if the bond relation has finish (termination costs), relation values, culture, and ethics (share value), formal and informal communication (communication), opportunistic behavior, satisfaction level that appeared in mutualism relation and cooperative. The data used in this study derived from 77 purchasing managers on garment industry in Indonesia, in which collaborative relationship on this industry is determinant to increasing product quality, indeed, become important factor to success in future. Linier regression analysis has used to test hypothesis this study. The conclusion of this study revealed that the industry try to increase trust and commitment in relation its supplier shall underline by good communi-cation, on time, relevant, and obey to ethics, culture, and values (share value) of the relation. Beside that, both sides shall adaptive to adjust their desire and need, and make mutualism cooperative.